With Orca, Goose, and Bear: Expanding Canada's Ritual Body - Zentner-Barrett, Joshua (Toronto journal of theology, 2025)
The publication of the Truth and Reconciliation Commission of Canada in 2015 was a significant moment in both the story of Canadian-Indigenous relations and church-Indigenous relations. Churches across Canada have been wrestling not only with their complicity in the operation of residential schools but with their wider role in European colonialism. Many of the churches have initiated significant strategies for learning and education, and have explored ritual responses to residential schools and colonialism, such as land acknowledgements, art installations, and the reading of parts of the Truth and Reconciliation Commission of Canada. This paper is not quite about these ritual practices. Instead, it takes a wider lens, asking about the context in which these practices take place: what does it mean to "do" liturgy—to practice Christian ritual, to ritualize—in Canada today? More broadly, however, it asks how settler colonialism—particular practices of violence and domination—impact ritualization in contexts across the world—and how this is all rooted in the land. This paper proceeds in three parts. First, it discusses the concepts of the body, ritualization, and contextualization in Catherine Bell's Ritual Theory, Ritual Practice. Second, it examines settler colonialism using my own context of Canada as a particular example. Third, it draws on Cláudio Carvalhaes’ concept of lex naturae to expand Bell's concept of the "body": all (liturgical) practice must be seen through the lens of creation. Through a brief case study, it then demonstrates one way in which a Christian community has attempted to bring the voice of the land into liturgical practice and thus expand the ritualization of "bodies" in Christian ritual. Because of the way that settler colonialism functions in its global contexts, ritualization should understand the "body" as including the land and the interrelationship of all created things.